PERUBAHAN SOSIAL NILAI BUDAYA ADAT NYAHANG UMAH 19 SAGALO BATIN MASYARAKAT DUSUN BARU KECAMATAN TABIR - Maryam, Siti; Adnan, Adnan; Sinaga, Rudi Salam (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2023)
The implementation of this research is directed to explain the social changes in the cultural values of the nyahang umah 19 sagalo inner culture of the people of Dusun Baru, Tabir District. As well as to find out the factors that cause social change in the customary cultural values of nyahang umah 19 sagalo inner community of Dusun Baru, Tabir District. Baru Hamlet, Tabir District, Merangin Regency was used as a research location because Inner Rantau Panjang is the largest inner heart in Tabir District and still maintains local wisdom in maintaining the preservation of community culture. Currently, the legitimacy of traditional institutions is still strong in maintaining traditional values, and they are obeyed and respected as part of the traditional political elite. This research was conducted from January to March 2021. The results of this research are changes in the social values of the adat nyahang umah 19 sagalo inner community of the Baru Hamlet, Tabir Adat District, which can be seen from the nyahang umah custom, which has become a form of community concern for neighbors in the face of disaster. A community belief that the occurrence of a disaster is due to an intentional or unintentional mistake made by the family, so that the community reprimands it through advice to be patient in dealing with the disaster that occurs, and not to repeat it in the future. Then the community or neighbors who know about the incident will carry out nyahang umah to remind homeowners to admit their mistake. In this activity all the neighbors came to see/visit the person who had the disaster, then proceeded to eat white porridge as a sign of wrongdoing from the home owner.